Eliminable-Noise Dithering in MASH Digital Delta-Sigma Modulator Based on Error-Feedback Modulator - Achanapornkul, Suphom; Kongpoon, Metha (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2025)
Conventional LFSR-based dithering in the digital delta-sigma modulator (DDSM) is widely used to suppress spurious tones in the DDSM at the expense of the increased modulator’s noise floor. In this work, we present a new dithering technique using the error feedback modulator (EFM) that can both suppress spurious tones and eliminate the dithering noise. The proposed technique also offers the precise frequency-tuning ability beneficial for fractional-N frequency synthesizers. Moreover, the hardware complexity of the DDSM using the proposed dithering technique can be reduced significantly with multistage dithering and a short wordlength. Simulation results confirm that the proposed technique efficiently suppresses spurious tones without raising the noise floor for all inputs. The mathematic proof of the sequence length is also given to show that the maximum sequence length can be achieved for all inputs.